Reconstructing the Roman London flavourscape: new insights into the exotic food plant trade using network and spatial analyses - Livarda, Alexandra; Orengo, Hèctor A. (Elsevier, 2015)
Using archaeobotanical data and examining them with a novel combination of density interpolation surfaces and social and spatial network analyses, this study has brought together exotic food plants in Roman London to outline the changing ‘face’ of its flavourscape, and contextualise it within the broader exotics commerce in Britannia. Consumption of a variety of exotics appeared to be widespread since the very first stages of London's establishment and their presence was maintained throughout although later on, as life in the town developed and its character changed, the focus of their distribution also changed. The emphasis shifted from the core of the city in its early days towards its outer zones, such as the upper Walbrook valley and Southwark in the Middle Roman, and the western and eastern sectors in the Late Roman phase. These changes appeared to largely reflect the changes in the overall commerce network of exotics in Britannia. In this network London starts as a mainly consumption place in the Early Roman phase to become the main redistribution centre in the Middle Roman and the necessary intermediate node in the transport system that had been established by the Late Roman phase, connecting the south to the north.